Protein, vitamin and mineral fortification of bottled fruit juice blend using spirunila, arthospira platensis - Lim, Flordeliza Ocampo
ABSTRACT To aid in addressing the problem of micro nutrient malnutrition in the Philippines, the fortification of a bottled fruit juice blend with protein, vitamins and minerals using spirulina (Arthrospira platensis) was performed. The Pineapple-Banana Breeze (PBB) fruit juice blend, fortified at a level of 0.16% was found to have the taste most compatible with spirulina. Improvements on its sensory aspects were then effected to increase its acceptability rating. The replicability of the production procedure was confirmed. Assessment of the physico-chemical properties of the fortified PBB showed that pH was 2.87, titratable acidity was 0.48% citric acid, total soluble solids was 15 °Bx and Munsell color notation was 10 GY 6/6. Microbial examinations performed after one- and too-week storage showed that the fortified PBB was still safe for human consumption. High Performance Liquid Chromatography showed 28.57% increase in the Vitamin A contnet over that of the basic formulation. A serving portion (250ml) of the fortified PBB contributed 12.86% and 15% (significant) of the Philippine RDA. Atomic Absorption Spectroscopy showed that the fortified PBB exhibited a 154.76% increase in iron content and a 7.46% increase in manganese content. However, a serving portion still contributed insignificant percentages of the Philippine and WHO RDAs for iron and manganese, respectively, while contributing significantly to chromium intake based on the US RDA. The crude protein content of the fortified PBB increased by 842.86%- to contribute only 2.69% of the FAO/WHO/UNO Safe Protein Intake for Human Adults.